2011
DOI: 10.1098/rsta.2010.0318
|View full text |Cite
|
Sign up to set email alerts
|

Mutation-periodic quivers, integrable maps and associated Poisson algebras

Abstract: We consider a class of map, recently derived in the context of cluster mutation. In this paper, we start with a brief review of the quiver context, but then move onto a discussion of a related Poisson bracket, along with the Poisson algebra of a special family of functions associated with these maps. A bi-Hamiltonian structure is derived and used to construct a sequence of Poisson-commuting functions and hence show complete integrability. Canonical coordinates are derived, with the map now being a canonical tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…A recent development was the observation in [8] that (with all β i = 0) a combination of these compatible brackets for the dressing chain coordinates J i arises by reduction from the log-canonical Poisson structure for the cluster variables in cluster algebras associated with affine A-type Dynkin quivers. In this context, a further observation was that the linear relations between cluster variables found in [9] (see also [2,7,16]), which are of the form…”
Section: Connection With the Dressing Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent development was the observation in [8] that (with all β i = 0) a combination of these compatible brackets for the dressing chain coordinates J i arises by reduction from the log-canonical Poisson structure for the cluster variables in cluster algebras associated with affine A-type Dynkin quivers. In this context, a further observation was that the linear relations between cluster variables found in [9] (see also [2,7,16]), which are of the form…”
Section: Connection With the Dressing Chainmentioning
confidence: 99%
“…In [7], it was shown that theà 1,N −1 exchange relations produce integrable maps for N even; in the non-commutative setting, the exchange relations for N odd were considered in [3]. The simplest case (N = 2) is just the recurrence (1.2), which preserves the Poisson bracket {x n , x n+1 } = x n x n+1 , and has a conserved quantity C (independent of n) that appears as a non-trivial coefficient in the linear relation for the sequence of cluster variables (x n ), that is,…”
Section: Introductionmentioning
confidence: 99%
“…The following can be deduced from the quantum counterpart, Lemma 6.5, by taking the semiclassical limit or directly from (22). Parts (i) and (iv) were observed by Fordy in [12]. Lemma 8.2.…”
Section: Commutative Cluster Algebras With Poisson Structurementioning
confidence: 99%
“…, x n ] that are semiclassical limits of the families L q n and C q n . The Poisson algebra that is the semiclassical limit of C q 2 n was introduced by Fordy [12] and this sparked our interest in C q n . In this section we shall present results of an analysis of the Poisson prime spectrum of the semiclassical limits of L q n and C q n .…”
Section: Poisson Structuresmentioning
confidence: 99%
See 1 more Smart Citation